Persepsi Siswa SMA Negeri 1 Padang terhadap Perpustakaan SMA Negeri 1 Padang - Alwira, Fanny; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractThe perception of the students of SMA 1 Padang towards the library of SMAN 1 Padang. First, the knowledge or understanding of students of SMAN 1 Padang towards the library is quite good, as seen from the agreed response of the students of SMAN 1 Padang regarding the library on the 3rd floor and the library provides many collections. Second, students responses to the library of SMAN 1 Padang are still not good, it can be sen from students responding negatively to the ease in finding the book they are looking for, because students still get difficulties when looking for books in the library of SMAN 1 Padang. Third, the library assessment by students of SMAN 1 Padang is still not good. This can be seen from the assessment of students who feel uncomfortable being in the library because of the music in the room which disturbs the concentration of students while reading and not all students of SMAN 1 Padang consider the existence of a library as supporting their academic achievement.Keywords: perception, library, studentsÂ